Gastronomy In The Perspective Of Local Wisdom Of Lampung Community - Putut Ary Sadewo; Bunyamin Maftuh; Elly Malihah Setiadi; Dadang Sundawa (Jurnal Mamangan, 2024)
Gastronomy is a study that covers various aspects such as food, culture, history, and identity of a society. In Lampung society, gastronomy is closely related to local values called piil pesenggiri, which is a philosophy of life that emphasizes honor, dignity, and social solidarity. This study aims to understand the relationship between traditional Lampung cuisine and the values of piil pesenggiri in building the cultural identity of the local community. Traditional foods such as seruit, tempoyak, and kemplang crackers are not just dishes, but also a medium to maintain togetherness and social harmony. With a qualitative approach through literature studies and interviews with Lampung community leaders, this study found that values such as deliberation, togetherness, and respect for nature are manifested in the practice of serving, consuming, and preserving traditional foods. This shows that gastronomy is not only part of culture, but also a tool to strengthen local identity and preserve local wisdom in facing changing times. This study shows that culinary in Lampung society has a broader role than just fulfilling food needs. This cuisine also reflects the local wisdom contained in the philosophy of Piil Pesenggiri, which emphasizes the values of honor, togetherness, and responsibility. The novelty of this study Food in Lampung has a deep symbolic meaning, especially in various traditional events, such as weddings and thanksgiving, where food serves to strengthen social relationships and show respect to guests.